COMPETENCIAS CLAVES PARA LA GESTIÓN EMPRESARIAL DE LAS MYPES - Miranda Castillo, Robert (2005)
Micro and small companies represent approximately a 98% of the total amount of enterprises in Peru by generating by the 75% of employment and contribute round 44% of the enterprise generated income revenue. Export micro and small Companies imply 1674 ones from a total amount of 3057 companies however because of their sales size its market participation is a little meaningful and having export participation by less than a 1%. It’s a must to assess, understand both challenges and nature when to micro and small Companies demands to break some paradigms are concerned to settle new pertaining and value generating strategies by considering social responsibility. Main axis on purposes from human potential and development to develop management capacities, identify and perform market prospective and display a state, local governments support structure having intellectual and industrial rights as one of the system supports on the business development.